Evaluation of Altruistic Behavior for Kindergartens Children from their Mothers & Teachers Point of view (Journal of the College of Education for Women, 2019)
Abstract This study is aim to :Put a standard to evaluate the altruistic behavior in kindergarten children.Know level of the altruistic behavior in the kindergarten children according to their mother "s points of view.Know the level of the altruistic behavior in the kindergarten children according to their teacher "s points of view.The differences in the level of altruistic behavior in kindergarten children between their mothers & teachers points of view. The sample consists of (120) children of kindergarten children in Baghdad. The researcher has built a tool to evaluate the altruistic behavior in the children , then she got the psychometric characteristics for it . The results showed that the children haven't an altruistic behavior according to their mother "s points of view , while they have altruistic behavior according to their teacher "s points of view & there is differences between the mothers & teachers opinions for the teachers opinions . The researcher recommended that the curriculums of kindergarten should emphasize on the altruistic as a moral behavior have to instill inside children , in addition to urge the media to present programs on altruistic behavior to make it common in the society .Key words : Altruistic behavior ,Kindergarten children